Pembuatan Prototipe Mesin Pengaduk Baglog Jamur Tiram - Zulhendri, Zulhendri; Sukriman, Anil; Yuliarman, Yuliarman; Restu Araliz, Maheka; Yetri, Yuli (Manutech : Jurnal Teknologi Manufaktur, 2025)
A baglog mixing machine is a machine or tool used to stir oyster mushroom planting media. The aim of making this machine is to make it more effective and streamline the time and energy of oyster mushroom farmers. The ingredients contained in oyster mushroom seeds are rice bran, mahogany sawdust, rice bran and agricultural lime. For the stirring system, steel is used which is rotated using an electric motor. This machine has a door at the bottom of the container to make it easier to remove the baglog mixing results. This machine is designed to be ergonomic, easy to use and safe for operators when working on this machine. It is hoped that the existence of this oyster mushroom baglog mixing tool or machine can help increase the amount of oyster mushroom baglog production and ease the work of oyster mushroom entrepreneurs. This machine has a volume capacity of 100 kg of oyster mushroom baglog and takes 20 minutes for one stir.